HUKUM ADMINISTRASI NEGARA SEBAGAI HIMPUNAN PERATURAN-PERATURAN ISTIMEWA - Chandra Aritonang (Fakultas Hukum Universitas Kristen Indonesia, 2019)
Abstract State Administration in every action must be based on law to solve and resolve the problem mentioned above or there is no law. The State Administration can be forced to use its authority to revoke regulations. Administration as a law maker in its application when related to legal systematics has caused controversial matters in essence State Administration is part of public law, so that all actions in the application based on its function are solely intended for and in the public interest, this is no different from the law State Administration, Criminal Law and Others. A situation can lead to deviations from the State administration of the systematics of law. Therefore the State Administrative Law as a set of special regulations. Keywords: state administration; public law; special regulations.